Cinema of enchantment : Perso-Arabic genealogies of the Hindi masala film - Roy, Anjali Gera
A fascinating account of the theatrical beginnings of Bollywood and the Indo-Islamic storytelling traditions of the subcontinent, the volume looks at how Islamicate cultures have richly informed and structured mainstream Hindi cinema. It tells us how it was Urdu which provided the language of quintessential romance, passion and poetry for it. Acknowledging the central contribution of Hindu mythology, narrative visual arts and epics on storytelling in film, the volume isolates Bollywood’s generic debt to the Perso-Arabic legacies of tilism or enchantment, qissa and dastan, which have been marginalised in the construction of popular Hindi cinema as national cinema. It looks at the structure and narrative form of Orientalist genres of the Silent period, stunt films, costume dramas, and their continuity in the ‘masala’ film of the 1960s and 1970s. As opposed to the lens of fantasy through which the dream-world of Hindi cinema has been traditionally perceived, it suggests that tilism may provide a framework for examining its magical and enchanting universe. The influence of Urdu writers, pre- and post Partition, Urdu poetry and Sufism on film scripts, dialogue and music ensured that the language of Firdausi, Ghalib and Zafar lived on in popular imagination. Bollywood, thus, provided one of the last havens for preserving and performing India’s famed syncretic ‘Ganga-Jamuni tehzeeb’—wherein Hindi and Urdu are not two but are deeply implicated in one another—even as it disappeared from other public spaces. The volume is addressed to students and scholars in the fields of cinema, culture and media studies, film history. Any reader interested in Hindi films and popular culture would also find it engaging and insightful.